BDKRB2 gene -9/+9 polymorphism and swimming performance - Grenda, A.; Leonska-Duniec, A.; Cieszczyk, P.; Zmijewski, P. (Biology of Sport, 2014)
The aim of the study was to evaluate the association between swimming performance and the -9/+9 (rs5810761) polymorphism within the BDKRB2 gene in successful competitive swimmers.Best individual swimming results expressed in FINA points achieved at short, middle and long distance events of 157 well-trained Polish swimmers were incorporated into an analysis. Athletes` genotype and allele distributions were analysed in comparison to 230 unrelated sedentary subjects who served as controls with the ?2 test. All samples were genotyped for the BDKRB2 -9/+9 polymorphism using the polymerase chain reaction (PCR). The effects of genotype on swimming performance were analysed with two-way (3 x 2; genotype x gender) analysis of variance with metrical age as a covariate for each distance specialization. No statistical differences in the genotype and allele frequencies were found in long distance swimmers when compared with the total group of swimmers or controls. The BDKRB2 +9/-9 genotype had no significant effect on swimming performance at short, middle or long distance, regardless of gender. The results of this study do not support the hypothesis that the BDKRB2 -9/+9 polymorphism is associated with swimming performance in Polish swimmers.